2020
DOI: 10.1002/pbc.28732
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation in children and adolescents with nonremission acute lymphoblastic leukemia

Abstract: Background: The appropriateness of allogeneic hematopoietic stem cell transplantation (HSCT) in children and adolescents with leukemia in whom complete remission is not possible remains unclear. This retrospective analysis aimed to investigate the outcomes associated with HSCT, and the risks of HSCT in children and adolescents with nonremission acute lymphoblastic leukemia (ALL). Procedure: Data from the Japan Society for Hematopoietic Cell Transplantation registry on 325 patients with nonremission ALL (aged <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This is in clear contrast to BCP‐ALL patients receiving HSCT, for whom OS is almost always approximately 10% higher than LFS 7,32 . Notably, HSCT for patients with non‐CR disease at the time of HSCT showed a dismal outcome comparable to the recent report, although it has been regarded as one of the clinical options for patients with ALL in Japan 33 . These results indicate that HSCT for non‐CR disease should be avoided, and that preparing optimal HSCT settings during CR1 is crucial for these patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This is in clear contrast to BCP‐ALL patients receiving HSCT, for whom OS is almost always approximately 10% higher than LFS 7,32 . Notably, HSCT for patients with non‐CR disease at the time of HSCT showed a dismal outcome comparable to the recent report, although it has been regarded as one of the clinical options for patients with ALL in Japan 33 . These results indicate that HSCT for non‐CR disease should be avoided, and that preparing optimal HSCT settings during CR1 is crucial for these patients.…”
Section: Discussionmentioning
confidence: 63%
“…GVHD, graft-versus-host disease; NRM, non-relapse mortality outcome comparable to the recent report, although it has been regarded as one of the clinical options for patients with ALL in Japan. 33 These results indicate that HSCT for non-CR disease should be avoided, and that preparing optimal HSCT settings during CR1 is crucial for these patients.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the mortality rate at 100 days after transplantation was in ALL. Okamoto et al (23) reported a 3-year OS of 22% in children and adolescents with nonremission ALL. We believe that combined CAR-T cell therapy and HSCT has a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…receives super doses of chemotherapy and radiation to kill the malignant cells in their body. The collected autologous cells are then transfused back to rebuild hematopoietic and immune functions to cure patient (17,18). However, Cooley (19) found that there were very few malignant cells in the bone marrow or peripheral blood during the continuous remission period of leukemia, they could be regarded as "normal" cells, but they were also malignant cells.…”
Section: Discussionmentioning
confidence: 99%